Exploratory Modeling and Simulation to Support Development of Motesanib in Asian Patients With Non–Small Cell Lung Cancer Based on MONET1 Study Results. Issue 4 (17th January 2014) - Claret, L; Bruno, R; Lu, J‐F; Sun, Y‐N; Hsu, C‐P
<x xml:space="preserve">Abstract</x> The motesanib phase III MONET1 study failed to show improvement in overall survival (OS) in non–small cell lung cancer, but a subpopulation of Asian patients had a favorable outcome. We performed exploratory modeling and simulations based on MONET1 data to support further development of motesanib in Asian patients. A model‐based estimate of time to tumor growth was the best of tested tumor size response metrics in a multivariate OS model (P < 0.00001) to capture treatment effect (hazard ratio, HR) in Asian patients. Significant independent prognostic factors for OS were baseline tumor size (P < 0.0001), smoking history (P < 0.0001), and ethnicity (P < 0.00001). The model successfully predicted OS distributions and HR in the full population and in Asian patients. Simulations indicated that a phase III study in 500 Asian patients would exceed 80% power to confirm superior efficacy of motesanib combination therapy (expected HR: 0.74), suggesting that motesanib combination therapy may benefit Asian patients. Clinical Pharmacology & Therapeutics (2014); 95 4, 446–451. doi:10.1038/clpt.2014.11